Smart learning - Chan, Jerome Chun Hou (Nanyang Technological University, 2020)
This project aims to create a mobile application that functions as both a means for data collection for future researchers/educators and as a study analysis companion for students to benefit from. For the researcher side, the mobile application will be focused on accurately collecting information on the students during their studying periods, including external factors such as location, if the student is studying alone or in a group and time spent distracted while studying. The data gathered from this application can then be used to properly analyze and provide valuable insight on studying habits and how they can affect academic performance. For the students, it would function as a method for them to have more information available to them about the work required to excel in their current courses, as well as analyze their own studying habits. This would make them more aware of how much time and effort they are putting into their studies, thus they can then make productive changes that would benefit them. Development of the application will be done in Android using React Native and Firebase as the database.